The Development of Interactive Multimedia Mobile Learning about Bacterial Topic to train the Students' Ability of Science Literacy - Merinda Oktaviana; Murni Sapta Sari; Sunarmi Sunarmi (Universitas Negeri Malang, 2020)
Science literacy is a human's ability to understand science and use that understanding to be applied in solving a problem in everyday life. Students' science literacy skills are low due to the student's response in answering a question to explain the phenomenon has not fulfilled the aspects of science literacy. This research aims to develop an interactive multimedia Mobile Learning that is valid, practical, and effective in making students practice their science literacy skills. Interactive multimedia research and development of the Mobile Learning model uses a Research and Development model that adapts the development model of William W. Lee and Diana L. Owens. The stages of development in the model of Lee and Owens are (1) Assessment/Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The results of this research and development obtained 97.8 percent validation value of media experts, obtained a validation value of 100 percent by topic experts, also earned an average of 94 percent value in the validation of expert assessment. So that based on the data results of this development research was very valid category the field-test results of research and development conducted with the researchers as a teacher for two meetings produced a practical test value by students of 84.42 percent, a very practicable category. The practicality test results (field practitioner) obtained a value of 100 percent, which was a very practical category. The value of effectiveness test in this study obtained an N-gain value of 16.74, which belonged to the low category (low effective).